MANFAAT PERHUTANAN SOSIAL (STUDI KASUS HUTAN KEMASYARAKATAN SIKAYAN BALUMUIK) DI KOTO BARU, KELURAHAN LIMAU MANIS SELATAN, KECAMATAN PAUH, KOTA PADANG - Difa Kurnia; Paus Iskarni (JURUSAN GEOGRAFI FIS UNP, 2020)
The research aims to discuss the benefits of social forestry.(Public forest Case study Sikayan Balumuik) in Koto Baru, village of Limau Manis Selatan, Pauh Sub-district, Padang. Methods are used in a descriptive method with a quantitative approach.Variables in this study are the characteristics of community forest areas,Community knowledge that is incorporated as a member of the group and the benefit of public forest. The sample determination in the study was conducted using the total sampling method.The data collection techniques used are technique of map layout and questionnaireThe results of the study obtained social forestry benefit (the case study of public forest Sikayan Balumuik in Koto Baru The southern Sweet Limau, Pauh Sub-district, Padang City is the physical characteristics of the public forest Sikayan Balumuik is in the slope 15%-25%, 25%-40% and 40% or more, soil type Incepisol and Ultisol, rainfall 4500 – 5000 mm / year, Mountain Rock Geology of the older Quarter Ape (Qv) Leleobasso/Ssedimen Jura (Js) the alluvium (Qf) fan, the use of primary natural forest land, and non-forest forests that have been.The knowledge of communities incorporated into community forest groups has a fairly good level of knowledge with a percentage 71.4%. No side work and the utilization of forest and land contributed to 50 – 100% . Then the benefit of the community forest in see from the side work of the 70% of community forest Farmer Group Sikayan Balumuik Monthly expenditure on the public forest farmer group Sikayan Balumuik.